*Note:- 1) If y = sinx ; then dy/dx = cosx *

*2) If y = cosx ; then dy/dx = -sinx*

*3) If y = u*v ; where both u & v are functions of 'x' , then*

*dy/dx = u*(dv/dx) + v*(du/dx)*

*4) If y = k ; where 'k' = constant ; then dy/dx = 0*

*5) cos(pi/2) = sin(pi) = 0*

*6) sin(pi/2) = 1 & cos(pi) = -1*

Now, the given function is :-

y*sin(2x) = x*cos(2y)

Differentiating both sides w.r.t 'x' we get

{sin(2x)}*(dy/dx) + 2y*cos(2x) = cos(2y) - 2x*{sin(2y)}*(dy/dx)

Putting x = pi/2 & y = pi/4 in the above equation we get

dy/dx = slope of the tangent at point (pi/2,pi/4) = 1/2

Thus, the eqaution of the tangent at the point (pi/2,pi/4) is:-

y - (pi/4) = (1/2)*{x - (pi/2)}

y = (1/2)*x = tangent equation

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now